Empirical Amphotericin B therapy on Day 4 or Day 8 of Febrile Neutropenia. Issue 2 (11th July 2013) - Malhotra, Pankaj; Makkar, Akash; Guru Murthy, Guru Subramanian; Varma, Neelam; Varma, Subhash; Chakrabarti, Arunaloke
Summary Febrile neutropenic patients are at greater risk of getting bacterial and fungal infections. Empirical antifungal therapy is considered if the fever persists despite broad‐spectrum antibiotics including vancomycin. However, the timing of initiating empirical antifungal therapy can vary from 3 to 8 days of non‐response to antibiotics. We choose to determine the response of empirical amphotericin B deoxycholate (dAMB) starting either on day 4 or day 8 in febrile neutropenic patients not responding to broad‐spectrum antibiotics and without localisation of fever. Fifty‐six patients with persistent neutropenic fever despite 72 h of antibiotic therapy were randomly assigned to receive dAMB either starting on day 4 (group A, n = 27, median age 23 years) or starting on day 8 (group B, n = 29, median age 25 years). Satisfactory response (patient remaining afebrile for 48 h and maintaining absolute neutrophil count >500 μl−1) occurred in 85.2% of patients in group A vs. 69.5% in group B (P = 0.209). Patients in group A took significantly fewer days to become afebrile than group B (5.4 ± 3.9 days vs. 11.3 ± 4.0 days, P = 0.0001). The adverse side effects of dAMB (nephrotoxicity, hypokalemia and hypomagnesemia) occurred at similar rates in both groups. Early addition of empirical dAMB in febrile neutropenic patients leads to their early defervescence and decreased dose requirement.